Crescendo of the Virtuoso: Spectacle, Skill, and Self-Promotion in Paris During the Age of Revolution - Metzner, Paul (California University of California Press, 1998)
During the Age of Revolution, Paris came alive with wildly popular virtuoso performances. Whether the performers were musicians or chefs, chess players or detectives, these virtuosos transformed their technical skills into dramatic spectacles, presenting the marvelous and the outré for spellbound audiences. Who these characters were, how they attained their fame, and why Paris became the focal point of their activities is the subject of Paul Metzner's absorbing study. Covering the years 1775 to 1850, Metzner describes the careers of a handful of virtuosos: chess masters who played several games at once; a chef who sculpted hundreds of four-foot-tall architectural fantasies in sugar; the first police detective, whose memoirs inspired the invention of the detective story; a violinist who played whole pieces on a single string. He examines these virtuosos as a group in the context of the society that was then the capital of Western civilization.
Keywords: French Revolution (1789-1799); Paris (France)